Three can keep a secret [large type] - Hilliard, M. E. (Hilliard, M. E. Greer Hogan mystery, 2023)
"Greer Hogan is a librarian turned sleuth, an avid reader of crime fiction who possesses an uncanny knack for deduction--and now, she's drawn into another murder case as late autumn slowly turns to winter in the idyllic village of Raven Hill. When Anita Hunzeker, chair of the library board of trustees, is run off the road and killed, no one seems all that sorry. Anita was widely disliked, and the townsfolk would just as soon be rid of her. But when a local professor turns up dead as well, his connection to Anita and to other local residents leaves the suspect pool covering the entire county. Greer starts poking around, and the more she digs, the more it seems like everyone she knows is trying to hide something. When she unearths a clue in the old manor cemetery, she finally discovers the shocking truth--a cache of dark secrets stretching back decades that could rock the town to its core. Everyone who's come close to the truth has ended up dead--and if Greer doesn't tread lightly, she could be the next librarian to get archived for good. Drawing nostalgic inspiration from classic girl detective mysteries, Hilliard deftly captures notes of Agatha Christie and Dorothy L. Sayers in this third installment of the Greer Hogan mysterie"--